Hadith #139 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) proceeded from `Arafat till when he reached the mountain pass, he dismounted, urinated and then performed ablution but not a perfect one. I said to him, (“Is it the time for) the prayer, O Allah’s Messenger (ﷺ)?” He said, “The (place of) prayer is ahead of you.” He rode till when he reached Al-Muzdalifa, he dismounted and performed ablution and a perfect one, The (call for) Iqama was pronounced and he led the Maghrib prayer. Then everybody made his camel kne
Grade: Sahih

Hadith #181 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
“When Allah’s Messenger (ﷺ) departed from `Arafat, he turned towards a mountain pass where he answered the call of nature. (After he had finished) I poured water and he performed ablution and then I said to him, “O Allah’s Messenger (ﷺ)! Will you offer the prayer?” He replied, “The Musalla (place of the prayer) is ahead of you (in Al-Muzdalifa).
Grade: Sahih

Hadith #1244 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The daughter of the Prophet (p.b.u.h) sent (a messenger) to the Prophet (ﷺ) requesting him to come as her child was dying (or was gasping), but the Prophet (ﷺ) returned the messenger and told him to convey his greeting to her and say: “Whatever Allah takes is for Him and whatever He gives, is for Him, and everything with Him has a limited fixed term (in this world) and so she should be patient and hope for Allah’s reward.” She again sent for him, swearing that he should come. The Proph
Grade: Sahih

Hadith #1534 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
I asked, “O Allah’s Messenger (ﷺ)! Where will you stay in Mecca? Will you stay in your house in Mecca?” He replied, “Has `Aqil left any property or house?” `Aqil along with Talib had inherited the property of Abu Talib. Jafar and `Ali did not inherit anything as they were Muslims and the other two were non-believers. `Umar bin Al-Khattab used to say, “A believer cannot inherit (anything from an) infidel.” Ibn Shihab, (a sub-narrator) said, “They (`Umar and others) derived the a
Grade: Sahih

Hadith #1608 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
As soon as the Prophet (ﷺ) departed from `Arafat, he went towards the mountain pass, and there he answered the call of) the prayer is ahead of you (i.e. at asked, “O Allah’s Messenger (ﷺ)! Will you offer the prayer here?” He replied, “(The place of) the prayer is ahead of you (i.e. at Al-Muzdalifa).”
Grade: Sahih

Hadith #1610 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
I rode behind Allah’s Messenger (ﷺ) from `Arafat and when Allah’s Messenger (ﷺ) reached the mountain pass on the left side which is before Al-Muzdalifa he made his camel kneel and then urinated, and then I poured water for his ablution. He performed light ablution and then I said to him: (Is it the time for) the prayer, O Allah’s Messenger (ﷺ)!” He replied, “The (place of) prayer is ahead of you (i.e. at Al- Muzdalifa).” So Allah’s Messenger (ﷺ) rode till he reached Al-Muzd
Grade: Sahih

Hadith #1612 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) proceeded from `Arafat and dismounted at the mountainous pass and then urinated and performed a light ablution. I said to him, “(Shall we offer) the prayer?” He replied, “The prayer is ahead of you (i.e. at Al-Muzdalifa).” When he came to Al-Muzdalifa, he performed a perfect ablution. Then Iqama for the prayer was pronounced and he offered the Maghrib prayer and then every person made his camel kneel at his place; and then Iqama for the prayer was pronounced and
Grade: Sahih

Hadith #1810 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Once the Prophet (ﷺ) stood at the top of a (looked out from upon one) castle amongst the castles (or the high buildings) of Medina and said, “Do you see what I see? (No doubt) I see the spots where afflictions will take place among your houses (and these afflictions will be) as numerous as the spots where raindrops fall.”
Grade: Sahih

Hadith #2371 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Once the Prophet (ﷺ) stood at the top of one of the castles (or higher buildings) of Medina and said, “Do you see what I see? No doubt I am seeing the spots of afflictions amongst your houses as numerous as the spots where raindrops fall (during a heavy rain). (See Hadith No. 102)
Grade: Sahih

Hadith #2932 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
I asked the Prophet (ﷺ) during his Hajj, “O Allah’s Messenger (ﷺ)! Where will you stay tomorrow?” He said, “Has `Aqil left for us any house?” He then added, “Tomorrow we will stay at Khaif Bani Kinana, i.e. Al-Muhassab, where (the Pagans of) Quraish took an oath of Kufr (i.e. to be loyal to heathenism) in that Bani Kinana got allied with Quraish against Bani Hashim on the terms that they would not deal with the members of the is tribe or give them shelter.” (Az-Zuhri said, “K
Grade: Sahih

Hadith #3327 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Plague was a means of torture sent on a group of Israelis (or on some people before you). So if you hear of its spread in a land, don’t approach it, and if a plague should appear in a land where you are present, then don’t leave that land in order to run away from it (i.e. plague).
Grade: Sahih

Hadith #3446 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Once the Prophet (ﷺ) stood on one of the high buildings (of Medina) and said, “Do you see what I see? I see affliction pouring among your hours like raindrops.”
Grade: Sahih

Hadith #3574 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
That the Prophet (ﷺ) used to take him (i.e. Usama) and Al-Hassan (in his lap) and say: “O Allah! Love them, as I love them.”
Grade: Sahih

Hadith #3584 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
That the Prophet (ﷺ) used to take him and Al-Hasan, and used to say, “O Allah! I love them, so please love them,” or said something similar.
Grade: Sahih

Hadith #4087 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) sent us towards Al-Huruqa, and in the morning we attacked them and defeated them. I and an Ansari man followed a man from among them and when we took him over, he said, “La ilaha illal-Lah.” On hearing that, the Ansari man stopped, but I killed him by stabbing him with my spear. When we returned, the Prophet (ﷺ) came to know about that and he said, “O Usama! Did you kill him after he had said “La ilaha ilal-Lah?” I said, “But he said so only to save himsel
Grade: Sahih

Hadith #4360 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) rode a donkey, equipped with a thick cloth-covering made in Fadak and was riding behind him. He was going to pay visit to Sa`d bin Ubada in Banu Al-Harith bin Al-Khazraj; and this incident happened before the battle of Badr. The Prophet (ﷺ) passed by a gathering in which `Abdullah bin Ubai bin Salul was present, and that was before `Abdullah bin Ubai embraced Islam. Behold in that gathering there were people of different religions: there were Muslims, pagans, idol-wor
Grade: Sahih

Hadith #4892 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The Prophet (ﷺ) said, “After me I have not left any trial more severe to men than women.”
Grade: Sahih

Hadith #4988 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I stood at the gate of Paradise and saw that the majority of the people who entered it were the poor, while the wealthy were stopped at the gate (for the accounts). But the companions of the Fire were ordered to be taken to the Fire. Then I stood at the gate of the Fire and saw that the majority of those who entered it were women.”
Grade: Sahih

Hadith #5449 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The Prophet (ﷺ) rode a donkey having a saddle with a Fadakiyya velvet covering. He mounted me behind him and went to visit Sa`d bin ‘Ubada, and that had been before the battle of Badr. The Prophet (ﷺ) proceeded till he passed by a gathering in which `Abdullah bin Ubai bin Salul was present, and that had been before `Abdullah embraced Islam. The gathering comprised of Muslims, polytheists, i.e., isolators and Jews. `Abdullah bin Rawaha was also present in that gathering. When dust raised by
Grade: Sahih

Hadith #5736 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) rode a donkey saddled with a saddle covered with a Fadakiyya velvet sheet, and he made me ride behind him.
Grade: Sahih

Hadith #5775 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) used to put me on (one of) his thighs and put Al-Hasan bin `Ali on his other thigh, and then embrace us and say, “O Allah! Please be Merciful to them, as I am merciful to them. “
Grade: Sahih

Hadith #5972 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
That Allah’s Messenger (ﷺ) rode over a donkey covered with a Fadakiya (velvet sheet) and Usama was riding behind him. He was visiting Sa`d bin ‘Ubada (who was sick) in the dwelling place of Bani Al-Harith bin Al-Khazraj and this incident happened before the battle of Badr. They proceeded till they passed by a gathering in which `Abdullah bin Ubai bin Salul was present., and that was before `Abdullah bin Ubat embraced Islam. In that gathering there were Muslims, pagan idolators and Jews, an
Grade: Sahih

Hadith #6308 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I stood at the gate of Paradise and saw that the majority of the people who had entered it were poor people, while the rich were forbidden (to enter along with the poor, because they were waiting the reckoning of their accounts), but the people of the Fire had been ordered to be driven to the Fire. And I stood at the gate of the Fire and found that the majority of the people entering it were women.”
Grade: Sahih

Hadith #6361 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Once while I was with the Prophet (ﷺ) and Sa`d, Ubai bin Ka`b and Mu`adh were also sitting with him, there came to him a messenger from one of his daughters, telling him that her child was on the verge of death. The Prophet (ﷺ) told the messenger to tell her, “It is for Allah what He takes, and it is for Allah what He gives, and everything has its fixed time (limit). So (she should) be patient and look for Allah’s reward.”
Grade: Sahih

Hadith #6413 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Once a daughter of Allah’s Messenger (ﷺ) sent a message to Allah’s Messenger (ﷺ) while Usama, Sa`d, and my father or Ubai were (sitting there) with him. She said, (in the message); My child is going to die; please come to us.” Allah’s Messenger (ﷺ) returned the messenger and told him to convey his greetings to her, and say, “Whatever Allah takes, is for Him and whatever He gives is for Him, and everything with Him has a limited fixed term (in this world): so she should be patient
Grade: Sahih

Hadith #6519 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
the Prophet (ﷺ) said, “A Muslim cannot be the heir of a disbeliever, nor can a disbeliever be the heir of a Muslim.”
Grade: Sahih

Hadith #6617 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) sent us (to fight) against Al-Huraqa (one of the sub-tribes) of Juhaina. We reached those people in the morning and defeated them. A man from the Ansar and I chased one of their men and when we attacked him, he said, “None has the right to be worshipped but Allah.” The Ansari refrained from killing him but I stabbed him with my spear till I killed him. When we reached (Medina), this news reached the Prophet. He said to me, “O Usama! You killed him after he had sai
Grade: Sahih

Hadith #6796 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
Once the Prophet (ﷺ) stood over one of the high buildings of Medina and then said (to the people), “Do you see what I see?” They said, “No.” He said, “I see afflictions falling among your houses as rain drops fall.”
Grade: Sahih

Hadith #7096 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
We were with the Prophet (ﷺ) when suddenly there came to him a messenger from one of his daughters who was asking him to come and see her son who was dying. The Prophet (ﷺ) said (to the messenger), “Go back and tell her that whatever Allah takes is His, and whatever He gives is His, and everything with Him has a limited fixed term (in this world). So order her to be patient and hope for Allah’s reward.” But she sent the messenger to the Prophet (ﷺ) again, swearing that he should come
Grade: Sahih

Hadith #7163 - Sahih al-Bukhari - Usama bin 'Umayr al-Hadhali (Sahih al-Bukhari)
A son of one of the daughters of the Prophet (ﷺ) was dying, so she sent a person to call the Prophet. He sent (her a message), “What ever Allah takes is for Him, and whatever He gives is for Him, and everything has a limited fixed term (in this world) so she should be patient and hope for Allah’s reward.” She then sent for him again, swearing that he should come. Allah’s Messenger (ﷺ) got up, and so did Mu`adh bin Jabal, Ubai bin Ka`b and ‘Ubada bin As-Samit. When he entered (the h
Grade: Sahih

Hadith #183 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
There is no god but Allah, I attacked him with a spear. It once occurred to me and I talked about it to the Apostle (ﷺ). The Messenger of Allah (ﷺ) said: Did he profess” There is no god but Allah,” and even then you killed him? I said: Messenger of Allah, he made a profession of it out of the fear of the weapon. He (the Holy Prophet) observed: Did you tear his heart in order to find out whether it had professed or not? And he went on repeating it to me till I wished I had embraced Islam
Grade: Sahih

Hadith #184 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
The Messenger of Allah may peace be upon him) sent us to Huraqat, a tribe of Juhaina. We attacked that tribe early in the morning and defeated them and I and a man from the Ansar caught hold of a person (of the defeated tribe). When we overcame him, he said: There is no god but Allah. At that moment the Ansari spared him, but I attacked him with my spear and killed him. The news had already reached the Apostle (peace be upon him), so when we came back he (the Apostle) said to me: Usama, did you
Grade: Sahih

Hadith #2022 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
While we were with the Messenger of Allah (ﷺ), one of his daughters sent to him (the Messenger) to call him and inform him that her child or her son was dying. The Messenger of Allah (ﷺ) told the messenger to go back and tell her that what Allah had taken belonged to Him, and to him belonged what He granted; and He has an appointed time for everything. So you (the messenger) order her to show endurance and seek reward from Allah. The messenger came back and said: She adjures him to come to h
Grade: Sahih

Hadith #2967 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
I was sitting behind Allah’s Messenger (ﷺ) on the riding animal from ‘Arafat. As Allah’s Messenger (ﷺ) reached the left side of the mountain which was situated near Muzdalifa, he made the camel kneel down and made water and then came back. I poured water and he, performed light ablution. I then said: Messenger of Allah, it is time for prayer. Thereupon Allah’s Messenger (ﷺ) said: The prayer awaits you (at the next station, Muzdalifa). Allah’s Messenger (may peaced be upon him) ro
Grade: Sahih

Hadith #2979 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Allah’s Messenger (ﷺ) on his way back from ‘Arafat got down in one of these creeks (to answer the call of nature), and after he had done that I poured water (over his hands) and said: Are you going to pray? Thereupon he said: The place of prayer is ahead of you.
Grade: Sahih

Hadith #2980 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
AHah’s Messenger (ﷺ) was on his way back from ‘Arafat and as he reached the creek (of a hillock) he got down and urinated (Usama did not say that he poured water), but said: He (the Holy Prophet) called for water and performed ablution, but it was not a thorough one. I said: Messenger of Allah, the prayer! Thereupon he said: Prayer awaits you ahead (at Muzdalifa). He then proceeded, until he reached Muzdalifa and observed sunset and ‘Isha’ prayers (together) there.
Grade: Sahih

Hadith #2982 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Messenger of Allah, the prayer I Thereupon he said: Prayer awaits you ahead.
Grade: Sahih

Hadith #3172 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Will you stay in your house at Mecca (which you abandoned at the time of migration)? Thereupon he said: Has ‘Aqil left for as any land or house? And ‘Aqil and Talib became the Inheritors of Abu Talib’s (property), and neither Ja’far nor ‘Ali inherited anything from him, for both (Ja’far and ‘Ali) were Muslims whereas ‘Aqil and Talib were non-Muslims.
Grade: Sahih

Hadith #3173 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Allah’s Messenger, God willing, where will you stay tomorrow? And it was at the time of the Conquest (of Mecca). Thereupon he (the Holy Prophet) said: Has ‘Aqil left any accommodation for us?
Grade: Sahih

Hadith #3174 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Usama b. Zaid (Allah be pleased with him) said: Allah’s Messenger, God willing, where will you stay tomorrow? Thereupon he (the Holy Prophet) said: Has ‘Aqil left any accommodation for us?
Grade: Sahih

Hadith #4011 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
A Muslim is not entitled to inherit from a non-Muslim, and a non-Muslim is not entitled to inherit from a Muslim.
Grade: Sahih

Hadith #4528 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Do not scatter the dust over us (Not minding this remark), the Prophet (ﷺ) greeted them, stopped, got down from his animal, invited them to Allah, and recited to them the Qur’an. ‘Abdullah b. Ubayy said: O man, if what you say is the truth, the best thing for you would be not to bother us with it in our assemblies. Get back to your place. Whoso comes to you from us, tell him (all) this. Abdullah b. Rawaha said: Come to us in our gatherings, for we love (to hear) it. The narrator says: (At
Grade: Sahih

Hadith #5624 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Plague is the sign of a calamity with which Allah, the Exalted and Glorious, affects people from His servants. So when you hear about it, don’t enter there (where it has broken out), and when it has broken out in a land and you are there, then don’t run away from it.
Grade: Sahih

Hadith #5625 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
Plague is a calamity which was inflicted on those who were before you, or upon Bani Isra’il. So when it has broken out in a land, don’t run out of it, and when it has spread in a land, then don’t enter it.
Grade: Sahih

Hadith #5628 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
This calamity or illness was a punishment with which were punished some of the nations before you. Then it was left upon the earth. It goes away once and comes back again. He who heard of its presence in a land should not go towards it, and he who happened to be in a land where it had broken out should not fly from it.
Grade: Sahih

Hadith #6767 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
I stood at the door of Paradise and I found that the overwhelming majority of those who entered therein was that of poor persons and the wealthy persons were detained to get into that. The denizens of Hell were commanded to get into Hell, and I stood upon the door of Fire and the majority amongst them who entered there was that of women.
Grade: Sahih

Hadith #6775 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
I have not left after me any (chance) of turmoil more injurious to men than the harm done to the men because of women.
Grade: Sahih

Hadith #6776 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
I have not left after me turmoil for the people but the harm done to men by women.
Grade: Sahih

Hadith #7066 - Sahih Muslim - Usama bin 'Umayr al-Hadhali (Sahih Muslim)
You do not see what I am seeing and I am seeing the places of turmoil between your houses as the places of rainfall.
Grade: Sahih

Hadith #140 - Sunan al-Nasa'i - Abu al-Malih; Qatada قتادة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Usama bin 'Umayr al-Hadhali; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘Allah does not accept Salah without purification, nor charity from Ghulul.'” That which is taken from the spoils of war prior to their distribution.
Grade:

Hadith #854 - Sunan al-Nasa'i - Abu al-Malih; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Usama bin 'Umayr al-Hadhali (Sunan al-Nasa'i)
“I heard the Messenger of Allah (ﷺ) say: ‘If any one of you feels the need to defecate, let him do that first, before he prays.”‘
Grade:

Hadith #2524 - Sunan al-Nasa'i - Abu al-Malih; al-Husain bin Muhammad al-Dhara' الحسين بن محمد بن أيوب الذارع السعدي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Qatada قتادة; Usama bin 'Umayr al-Hadhali; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“I heard As-Sa’ib bin Yazid say: ‘During the time of Allah’s messenger, the Sa’ was equal to a Mudd and third of the Mudd you use today, and the Sa’ of today has become large.”‘ (Sahih) Abu ‘Abdur-Rahman (An-Nasa’i) said: And Ziyad bin Ayyub narrated it to me.
Grade:

Hadith #4253 - Sunan al-Nasa'i - Abu al-Malih; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Usama bin 'Umayr al-Hadhali; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
during the campaign of Tabuk, the Prophet of Allah called for water from a woman. She said: “I only have a waterskin of mine made from an (unslaughtered) dead animal.” He said: “Didn’t you tan it?” She said: “Of course.” He said: “Then it’s tanning is its slaughter”. (Daif)
Grade:

Hadith #4131 - Sunan Abi Dawud - Abu al-Malih; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Usama bin 'Umayr al-Hadhali; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Al-Miqdam ibn Ma’dikarib and a man of Banu Asad from the people of Qinnisrin went to Mu’awiyah ibn AbuSufyan. Mu’awiyah said to al-Miqdam: Do you know that al-Hasan ibn Ali has died? Al-Miqdam recited the Qur’anic verse “We belong to Allah and to Him we shall return.” A man asked him: Do you think it a calamity? He replied: Why should I not consider it a calamity when it is a fact that the Messenger of Allah (ﷺ) used to take him on his lap, saying: This belongs to me and Husayn bel
Grade: Sahih